Structural changes of brain vessels in cardiosurgery patients with postoperative stroke - Mankovskyi, Dmytro (ScienceRise: Medical Science, 2022)
Hypoxic-ischemic lesions of the brain of cardiac surgery patients as a leading factor in stroke have been studied. The importance of prolonged thrombosis, embolism, which exacerbate the general degenerative changes in the central nervous system is recognized. The aim of the research – to study the morphological changes of the vessels of the brain of cardiac surgery patients with postoperative stroke on the background of hypoxic-ischemic complications. Materials and methods. Pieces of cerebral vessels were subjected to microscopic examination. Histological sections were stained according to Van Gieson. Results and their discussion. The study of the structure of the vessels of the brain of persons who were in the group intact to neurological pathology control, showed the presence of anatomical and functional changes that are fully consistent with the sex-age norms of postnatal human ontogenesis. The drugs of the clinical observation group contained signs of pathological changes characteristic of hypoxic-ischemic disorders. It is obvious that their appearance and intensification contributed to the development of ischemic stroke. Structural and functional changes mainly concerned the vascular walls, their layers, paravasal spaces, the blood system as a liquid phase, in fact. Endothelial layer with signs of desquamation. Endothelial cells are characterized by signs of hyperchromia of the nuclei, the shift of the latter in the direction of one of the poles of the cells, the appearance of heterochromatin. Contacts between cells are weakened, defects are visible in the surface layer. Perovascular edema, which is formed in the case of increased permeability, leads to a certain isolation of individual vessels from the surrounding tissues, followed by the development of hypoxia. Defects of the wall layers lead to the activation of the migratory properties of platelets, encourage the appearance of megakaryocytes, erythrocyte thrombi, which are in close contact with the endothelial layer of blood vessels. On histological specimens, brick-red blood clots abundantly cover the damaged inner layer of vascular walls, sometimes completely filling their openings. Over time, defects in the layers of the walls are accompanied by thrombosis, inflammation, edema. Conclusions. Hypoxic-ischemic brain lesions in cardiac surgery patients play a leading role in stroke. Priority is given to hypoxia, which contributes to ischemia, trophic disorders, atrophy, necrosis, necrobiotic changes. The latter are the organic basis of pathogenetic patterns of focal cerebral infarction (with progressive destruction of brain cells, its vessels, the development of prolonged thrombosis, embolism, increased general degenerative changes in the central nervous system)